Lymphocyte-activating gene-3 expression is associated with tumor-infiltrating lymphocyte levels in HER2-positive breast cancers. Issue 50 (17th December 2021) - Lee, Seokwon; Kim, Jee Yeon; Lee, So Jeong; Kwon, Soon Wook; Jung, Ho Jin; Jung, Se Jin; Kim, Kyung Bin; Choi, Kyung Un; Lee, Chang Hun; Huh, Gi Yeong; Kim, Ahrong
Abstract : Abstract: Lymphocyte-activating gene-3 (LAG-3, CD223) is the third inhibitory receptor targeted for immunotherapy. Several clinical trials investigating the use of interventions targeting LAG-3 are underway. The exact signaling mechanism downstream of LAG-3 is largely unknown, especially in breast cancer. The prognostic significance of tumor-infiltrating lymphocytes (TILs) in breast cancer has been previously determined. Among 167 human epidermal growth factor receptor 2 (HER2)-positive breast cancer patients, 90 and 78 patients were positive and negative for the hormone receptor, respectively. LAG-3 mRNA and protein expression levels in TILs were evaluated by quantitative real-time polymerase chain reaction and immunohistochemistry, respectively, among 12 and 167 HER2-positive breast cancer samples, respectively. High expression of LAG-3 in TILs was significantly correlated with high levels of TILs ( P = .003) and an abundance of tertiary lymphoid structures around invasive components ( P = .014). In addition, high expression of LAG3 was significantly associated with positivity for programmed death-ligand 1 (PD-L1) in tumor cells, a high immunostaining score of PD-L1 in TILs, and a high total immunostaining score for PD-L1 in tumor cells and TILs (all, P < .001). High expression levels of LAG-3 mRNA were associated with high levels of TILs ( P = .091). LAG-3 protein expression was not a prognostic factor in HER2-positive breast cancers, and LAG-3 expression in TILs was significantly associated with the levels of TILs in HER2-positive breast cancer, although it was not a prognostic factor.